Verifikasi Laporan Keuangan: Akses Pendanaan dan Risiko Pada Usaha Kecil dan Menengah - Intan Restu Nurpramitha; Ronny Prabowo (AFRE (Accounting and Financial Review), 2019)
This study aims to analyze the effect of financial statement verification on small and medium enterprises’  (SMEs) access to finance. Total of all the initial samples was 144 SMEs. After eliminating the criteria, the final sample remaining to be used in this study was 1024 SMEs. This study is a quantitative, using data from The World Bank Indonesia Enterprise Survey 2009 with the ordinal regression test. The results show that financial statement verification positively affects SMEs’ access to finance. Thus, this study suggests the importance of financial statement verification for SMEs, especially to enhance their financing access as one of SME’s main problems. DOI: https://doi.org/10.26905/afr.v2i1.3009